Faktor-Faktor yang Memengaruhi Financial Statement Fraud - Nuraya, Adinda Sofi; Fachriyah, Nurul Sofi (Universitas Prasetiya Mulya, 2024)
Despite the lowest prevalence, according to a survey by ACFE in 2022, financial statement fraud causes the highest average total loss compared with other types of fraud. This research aims to provide the empirical evidence of the factors affecting financial statement fraud. The dependent variable is represented by the F-Score, and the independent variables represent factors affecting the financial statement fraud, including financial target, external pressure, ineffective monitoring, auditor changes, board of director’s changes. Using State-Owned Enterprises listed on the Indonesia Stock Exchange in 2019-2022as a sample,the research results shows that financial target has a positive effect on financial statement fraud, while auditor changes has a negative effect on financial statement fraud.